2004
DOI: 10.1128/mcb.24.19.8765-8777.2004
|View full text |Cite
|
Sign up to set email alerts
|

Early Activation of Sphingosine Kinase in Mast Cells and Recruitment to FcεRI Are Mediated by Its Interaction with Lyn Kinase

Abstract: Sphingosine kinase has been recognized as an essential signaling molecule that mediates the intracellular conversion of sphingosine to sphingosine-1-phosphate. In mast cells, induction of sphingosine kinase and generation of sphingosine-1-phosphate have been linked to the initial rise in Ca 2؉ , released from internal stores, and to degranulation. These events either precede or are concomitant with the activation of phospholipase C-␥ and the generation of inositol trisphosphate. Here we show that sphingosine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 52 publications
(62 reference statements)
2
74
0
Order By: Relevance
“…However, the evidence gathered to date suggests that a complex interplay of protein kinase-and lipid-derived signals are required in an apparent two step process in which SphKs translocate rapidly to plasma membranes and become active following FcεRI engagement (Olivera and Rivera, 2005;Olivera et al, 2006;Urtz et al, 2004). At the moment it has been difficult to resolve whether the translocation of SphKs to the plasma membrane is essential for activation or whether it is a consequence of activation.…”
Section: A Linking Fcεri To Sphingosine Kinase Activationmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the evidence gathered to date suggests that a complex interplay of protein kinase-and lipid-derived signals are required in an apparent two step process in which SphKs translocate rapidly to plasma membranes and become active following FcεRI engagement (Olivera and Rivera, 2005;Olivera et al, 2006;Urtz et al, 2004). At the moment it has been difficult to resolve whether the translocation of SphKs to the plasma membrane is essential for activation or whether it is a consequence of activation.…”
Section: A Linking Fcεri To Sphingosine Kinase Activationmentioning
confidence: 95%
“…At the moment it has been difficult to resolve whether the translocation of SphKs to the plasma membrane is essential for activation or whether it is a consequence of activation. Regardless, under circumstances where the stimulation of SphK by FcεRI is impaired there is also no translocation of SphK to membranes Urtz et al, 2004). We now know that the FcεRI-mediated translocation and activation of SphKs requires both Fyn and Lyn (Fig.…”
Section: A Linking Fcεri To Sphingosine Kinase Activationmentioning
confidence: 99%
“…Previous studies with human bone marrow-derived mast cells (29) and RBL-2H3 mast cells (13,16) have shown that SphK1 is primarily cytosolic and is rapidly translocated to the plasma membrane by Ag. Fc RI crosslinking activates both SphK1 and SphK2 and requires the Src protein tyrosine kinases Lyn (33) and Fyn (4). The finding that SCF, an important growth factor required for mast cell survival and differentiation, also activates SphKs (4) further emphasizes the importance of S1P in mast cells.…”
Section: Transport Of S1p By Abcc1 Influences Migration Of Mast Cellsmentioning
confidence: 99%
“…Following interaction with Lyn, SphK1 is recruited to membrane rafts where conformational changes may occur in both kinases that favor their respective activities. 8 Although activation of both SphK1 and SphK2 required Fyn kinase in murine BMMCs, only SphK1 activation was dependent on the adapter Grb2-associated binder 2 and phosphatidylinositol 3-kinase. 9 Based on results with fetal liver-derived MCs from SphK1 Ϫ/Ϫ , SphK2 Ϫ/Ϫ , and SphK1 Ϫ/Ϫ SphK2 Ϫ/Ϫ mice, it was suggested that SphK2, but not SphK1, may modulate calcium influx and downstream signaling, particularly PKC␣ and ␤, leading to degranulation and the production of eicosanoids and cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…4 In rodent MCs and human bone marrow-derived mast cells (BMMCs), aggregation of Fc⑀RI leads to activation of both isoforms of sphingosine kinase, SphK1 and SphK2, the enzymes that produce S1P from sphingosine. 4,[6][7][8] Down-regulation of SphK1 but not SphK2 in these MCs inhibits calcium mobilization, degranulation, and migration induced by Ag. 4,6,7 In human BMMCs and murine MCs, SphK1 translocates to the plasma membrane within minutes of Fc⑀RI clustering.…”
Section: Introductionmentioning
confidence: 99%